Targeting Cancer Cell Ferroptosis to Reverse Immune Checkpoint Inhibitor Therapy Resistance - Deng, Jingjing; Zhou, Mei; Liao, Tingting; Kuang, Wenlong; Xia, Hui; Yin, Zhengrong; Tan, Qi; Li, Yumei; Song, Siwei; Zhou, E; Jin, Yang (Frontiers in Cell and Developmental Biology, 2022)
In recent years, cancer therapies using immune checkpoint inhibitors (ICIs) have achieved meaningful success, with patients with advanced tumors presenting longer survival times and better quality of life. However, several patients still do not exhibit good clinical outcomes for ICI therapy due to low sensitivity. To solve this, researchers have focused on identifying the cellular and molecular mechanisms underlying resistance to ICI therapy. ICI therapy induces apoptosis, which is the most frequent regulated cell death (RCD) but lacks immunogenicity and is regarded as an “immune silent” cell death. Ferroptosis, a unique type of non-apoptotic-RCD, has been preliminarily identified as an immunogenic cell death (ICD), stimulating tumor-antigen-specific immune responses and augmenting anti-tumor immune effects. However, ferroptosis has rarely been used in clinical practice. Present evidence strongly supports that the interferon-γ signaling pathway is at the crossroads of ICI therapy and ferroptosis. TYRO3, a receptor tyrosine kinase, is highly expressed in tumors and can induce anti-programmed cell death (PD)-ligand 1/PD-1 therapy resistance by limiting tumoral ferroptosis. Therefore, in this review, we summarize the clinical practice and effects of ICI therapy in various cancers. We also provide an overview of ferroptosis and report the molecular connections between cancer cell ferroptosis and ICI therapy, and discuss the possibility to reverse ICI therapy resistance by inducing cancer cell ferroptosis.